PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS, PERTUMBUHANPERUSAHAAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - KRISTIANA, IRA (: 2303-1719)
Going concern indicates the company is able to maintain its business in the long run. If there is great doubt on the survival of the company, the auditor will issue a going-concern audit opinion. Issuance of going-concern audit opinion will influence investor decisions. Therefore, this study aims to examine the effect of firm-size, profitability, liquidity, and growth of the company’s going-concern audit opinion. Research design was quantitative with the hypothesis. The company studied is a manufacturing company listed on the Indonesia Stock Exchange with a period of 3 years from the year 2008-2010. The samples were selected by purposive sampling method. Data analysis was performed using logistic regression. The analysis showed that company size does not affect the going concern audit opinion, whereas profitability, liquidity and growth negatively affect the company's going-concern audit opinion.